Hitchcock's people, places, and things - Bruns, John (Northwestern University Press, 2019)
Hitchcock's people, places, and things argues that Alfred Hitchcock was as much a filmmaker of things and places as he was of people. Drawing on the thought of Bruno Latour, John Bruns traces the complex relations of human and nonhuman agents in Hitchcock's films with the aim of mapping his Hitchcock landscape cognitively, affectively, and politically. Yet this book does not promise that such a map can or will cohere, for Hitchcock was just as adept at misdirection as he was at direction. Bearing this in mind and true to the Hitchcock spirit, Hitchcock's people, places, and things anticipates that people will stumble into the wrong places at the wrong time, places will be made uncanny by things, and things exchanged between people will act as (not-so) secret agents that make up the perilous landscape of Hitchcock's work. This book offers new readings of well-known Hitchcock films, including The lodger, Shadow of a doubt, Psycho, The birds, and Marnie, as well as insights into less-discussed films such as I confess and Family plot. Additional close readings of the original theatrical trailer for Psycho and a Hitchcock-directed episode of Alfred Hitchcock presents expand the Hitchcock landscape beyond conventional critical borders. In tracing the network of relations in Hitchcock's work, Bruns brings new Hitchcockian tropes to light. For students, scholars, and serious fans, the author promises a thrilling critical navigation of the Hitchcock landscape, with frequent "mental shake-ups" that Hitchcock promised his audience.